IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM KURIKULUM MERDEKA KELAS IV DI SD NEGERI 1 TANJUNG SARI - Sani Aulia, Virda; Nurwahidin, Muhammad; Rika Perdana, Dayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Pancasila Student Profile Strengthening Project was a project-based learning activity that instilled Pancasila values through environmental issues. This program aimed to develop students' character, empathy, and social skills. This study aimed to analyze the strategies used by educators in implementing P5 at SD Negeri 1 Tanjung Sari and its impact on the character development of fourth-grade students. The research method used descriptive qualitative with a purposive sampling technique. Data sources were obtained through observations, interviews, and documentation studies. The subjects of the study included students, educators, the principal, P5 coordinators, and parents. The object of this study was the implementation of the Pancasila Student Profile Strengthening Project in the independent curriculum at SD Negeri 1 Tanjung Sari. The results of the study showed that the implementation of P5 was carried out through the strategies of organizing, interpreting, and applying. These three strategies had a positive impact on student character development, particularly in enhancing independence and learning motivation.